The Librarian and the Evaluation of a New Building. The University of Oslo Library and the Georg Sverdrup Building: Does the building support new challenges and new expectations? - Haugen, Eirin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The paper deals with the user (read: library) participation and influence on the building project, in particular the demands concerning the functionality of the building and the planning principles. An evaluation of how the building supports necessary changes in library organization of collections and services and new demands to the library will be made.